KAJIAN SISTEM CADANGAN PANGAN MASYARAKAT PEDESAAN DAN PERKOTAAN AKIBAT COVID 19 UNTUK MENGURANGI RESIKO KERAWANAN PANGAN DI MALANG RAYA - Arifin, Zainol; Khoirunnisa, Ninin (Universitas Tribhuwana Tunggadewi, 2023)
Along development Covid 19 which puts forward aspect Economy and aspect social, then serious attention. There is an impact on endurance food with an increased request for food society. So solution offered is to strengthen institutional food in the area by observing the existence of unrest in public due to covid-19. This study aims to analyze composite individual and vulnerability food for knowing the scarcity of food consequence covid 19, and the Vulnerability consequence impact covid 19 during a pandemic.Ln= α i X i +β Ability: Pi = method opportunities scale small to hold stash food because Pi = 1 for scale small that can be conducted stash food and P i = 0 for scale small that doesn't conduct stash food. X i = Model of the predicted factors that influence household do backup food among other things, level production commodity food, land assets, level income house stairs, commodity prices food, i = variable estimator. Method controller logistics (logs). Model by large with give logit. The study chooses Malang City and Regency Poor as region studies. Analysis to provision reduced impact level starving held to the up level as well as small tiers scale macro analysis developed on area base marriage on empirical also obtained by World Food Program (WFP). Analysis subtraction risks vulnerable food conducted with simulation from indicator starving food tree that can be controlled, and related including growth agrarian nor development in the sector agrarian. Results analysis obtained village data that still have potency for vulnerability food, with beware existence covid 19 so have scales namely 1, 2 and 3. which later will so the recommendation to districts city in Malangraya During the pandemic.